Icare: Building Synergy between Adab and Science in Early Childhood - Hesti Sunarti (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to: (1) describe how to familiarize with Islamic manners in Early Childhood Education, PAUD (Pendidikan Anak Usia Dini) students, (2) describe how to teach mastery of science competencies in PAUD students, and (3) describe the synergy between the habituation of Islamic manners and the mastery of science competencies through the application of the ICARE method in kindergarten students of grade B1 Shofa KB Islamic Kindergarten Al Azhar 28 Solo Baru. Theoretical framework: This research is based on the theoretical framework of constructivism which emphasizes the importance of the active role of children in building knowledge through meaningful social and environmental interactions. The ICARE (Introduction, Connect, Apply, Reflect, Extend) method is seen as aligned with this approach because it integrates cognitive and affective learning in a single set of fun and contextual activities. Literature review: Previous literature shows that habituation of character values from an early age has a significant impact on children's moral development, while mastery of science competencies is important to form the basis of logical and critical thinking. However, the integration of the two-in-one systematic learning approach is still rarely studied in depth. Methods: This study used a qualitative approach with data collection techniques in the form of in-depth interviews, participatory observations, and documentation. The subjects of the study are teachers and parents of B1 grade students at KB Islamic Kindergarten Al Azhar 28 Solo Baru. Results: The results show that: (1) the habituation of Islamic manners can be carried out effectively through parental assistance using the ICARE method in a pleasant learning atmosphere, (2) the mastery of science competence can also be improved through the same approach, and (3) there is a positive synergy between the habituation of Islamic manners and the mastery of scientific competence with the application of the holistic ICARE method. Implications: The implication of this study is the importance of collaboration between teachers and parents in character-based learning and science simultaneously. Novelty: The novelty of this research lies in the integration of Islamic manners and scientific competence in an ICARE-based methodological approach at the PAUD level, which has not been widely studied before.